Degradação de corantes da indústria alimentícia por processos oxidativos e redutivos: monitoramento por espectrometria de massas com ionização electrospray (ESI-MS) - Sergio Pinton Pavanelli (2010)
In this work, it was studied the degradation of some dyes used in food industry (brilliant blue, amaranth, sunset yellow and red 40) by means of oxidative (ozonolysis and combined Fenton) and reductive with zero valence metals (Fe0 and Sn0) and ultrasonic radiation processes. In the reductive processes, it was investigated the influence of the variables involved in the reaction conditions (exposure time to ultrasonic radiation and metal mass), using factorial design. This method allowed the investigation of the influence of these variables with a small number of experiments. The analysis by UV-Vis revealed that all the processes were very efficient in the degradation of the studied dyes. Degradation rates close to 100% were observed in most cases and all the assays have registered more than 90% values. Analysis of Total Organic Carbon(TOC) showed partial mineralization of the dyes aqueous solutions when subjected to different processes, thus indicating the formation of degradation products. The ESI-MS technique was effective for monitoring the dyes degradation and in some cases it was possible to identify by-products and to suggest degradation mechanisms. GC-MSwas used to monitor the ozonolysis of amaranth, a prototype azo dye. The results allowed a better understanding of this process.Ecotoxicity tests to Artemia salina revealed that all the dyes and their degradation products (via ozonolysis) present low toxicity while at lower levels. In higher concentrations, the brilliant blue degradation products presented the highest toxicity, and other dyes and their products showed moderate toxicity.